Pengaruh Pemberian Ekstrak Bengkuang (Pachyrhizus Erosus) sebagai Antioksidan terhadap Kadar Kolesteroltinggi pada Mencit (Mus Musculus) - Fardani, Roushandy Asri; Mentari, Ika Nurfajri; Fitria, Eka (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
High cholesterol levels in the blood are a serious problem because they are a risk factor for various non-communicable diseases such as heart disease, stroke and diabetes mellitus. Empirically, the secondary metabolic contents of jicama such as saponins& flavonoids have their respective properties. Saponin functions to bind cholesterol with bile acids so that it can reduce cholesterol levels. The results of the antioxidant activity test, the IC50 value of jicama extract is 115.20 mg/mL, which indicates that the antioxidant activity of jicama extract is classified as a moderate antioxidant. The results of measuring cholesterol levels after treatment showed that there was a decrease in cholesterol levels after giving jicama extract treatment in each group, seen in treatment 1 (P1) at 113.4 with a difference of 2.6 from cholesterol before administration, treatment 2 (P2) at 110.8 with a difference of 4.6 of cholesterol before administration, treatment 3 (P3) was 110.6 with a difference of 7.6 from cholesterol before administration of jicama extract, positive control (K+) was 108.4 with a difference of 30.2 from cholesterol before administration, negative control (K-) was 122.6 with a difference of 0.2 antioxidants from purple cabbage, namely 115.20 μg/mL. The antioxidant activity of purple cabbage is in the very strong category and vitamin C is in the very strong category.